Ratio of serum matrix metalloproteinases and their inhibitors in chronic insomnia patients (Annals of Medical Research, 2023)
Aim: Sleep is an essential part of a healthy life. Many people experience insomnia due to their living conditions. Matrix metalloproteinases (MMPs) play an essential role in remodeling the microenvironment. Tissue inhibitors of MMPs (TIMPs) maintain a balance with MMPs. Disruption of the balance causes various pathologies. The aim of the study is to elucidate the effects of sleep disturbance on matrix metalloproteinases and inhibitors by comparing MMP-2/TIMP-2 and MMP-9/TIMP-1 ratio in the serum of patients with chronic insomnia to healthy controls.Materials and Methods: This study included 40 adult males diagnosed with chronic insomnia and 40 healthy individuals as a control group. Blood samples were obtained from the brachial vein and subsequently centrifuged at 2,000 rpm for 15 minutes to collect serum samples. MMP-2, MMP-9, TIMP-1, and TIMP-2 levels were analyzed using commercial Enzyme-linked immunosorbent assay (ELISA) kit protocols with the obtained serum samples.Results: Consequently, in this study it was demonstrated a higher MMP-2/TIMP-2 ratio in chronic insomnia patients when compared to healthy controls, whereas the MMP-9/TIMP-1 ratio remained unchanged.Conclusion: These results suggest that higher MMP2/TIMP2 ratio may potentially contribute to the pathogenesis of diseases associated with sleep deprivation.
Keywords: Matrix metalloproteinase; Tissue inhibitors of MMPs; Chronic insomnia